Analysis of the Status of Radiation-generating Medical Devices in Mainland China. Issue 4 (15th April 2023) - Su, Yinping; Cui, Shiyue; Sun, Quanfu; Deng, Jun; Cheng, Jinsheng
Abstract: The purpose of this paper is to describe the status of radiation-generating medical devices in mainland China. The number of diagnostic radiology and interventional radiology devices was collected from the national medical radiation protection monitoring information system, while the number of radiation therapy and nuclear medicine devices was from the published articles. Statistical analysis of the correlation was used to assess the relationship between the number of high technology medical devices and GDP per capita. A total of 143, 064 radiation-generating medical devices were identified in mainland China, and diagnostic radiology devices accounted for 94% of those. The number of CTs was 14.84 per million, an increase by a factor of 1.45 compared to 2009. But the distribution of CTs was imbalanced among different areas: the highest number of CT per million population was 27.70 in Tibet, and the lowest was 8.55 per million population in Guangxi province. Statistical analysis of the correlation showed that the number of PET scanners per million population was positively correlated with GDP per capita, and similarly for medical accelerators. The number of mammographic devices per million population was much lower than that in other countries. The investment of radiation-generating medical devices in China was far from enough, especially for mammographic devices. More efforts should be taken to bring medical resources to regions with greater population areas in the future. Health Phys. 124(0):000-000; 2023